2016
DOI: 10.1080/09658211.2016.1177089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetition on age differences in associative recognition

Abstract: The study reported here examined the effect of repetition on age differences in associative recognition using a paradigm designed to encourage recollection at test. Young and older adults studied lists of unrelated word pairs presented one, two, four, or eight times. Test lists contained old (intact) pairs, pairs consisting of old words that had been studied with other partners (rearranged lures), and pairs consisting of two unstudied words (new lures). Participants gave old/new responses and then indicated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The associative REM model of Criss and Shiffrin (2005) appears to do well in capturing age differences in the effects of pair repetition on associative recognition. Although Overman and Becker (2009) found virtually no benefit of pair repetition for older adults in their experiment, other studies that have used a greater number of repetitions per pair have found some benefit of pair repetition in older adults (Kilb & Naveh-Benjamin, 2011;Light, Patterson, Chung, & Healy, 2004;Van Ocker, Light, Olfman, & Rivera, 2017). Can the associative REM model similarly use reduced feature diagnosticity to describe age differences in an experiment with additional pair repetitions?…”
Section: Effects Of Multiple Repetitionsmentioning
confidence: 86%
“…The associative REM model of Criss and Shiffrin (2005) appears to do well in capturing age differences in the effects of pair repetition on associative recognition. Although Overman and Becker (2009) found virtually no benefit of pair repetition for older adults in their experiment, other studies that have used a greater number of repetitions per pair have found some benefit of pair repetition in older adults (Kilb & Naveh-Benjamin, 2011;Light, Patterson, Chung, & Healy, 2004;Van Ocker, Light, Olfman, & Rivera, 2017). Can the associative REM model similarly use reduced feature diagnosticity to describe age differences in an experiment with additional pair repetitions?…”
Section: Effects Of Multiple Repetitionsmentioning
confidence: 86%
“…Among memory deficits, episodic memory performance undergoes the most pronounced changes with increasing age (Souchay et al, 2000; Daselaar et al, 2003; Kramer et al, 2003; Nilsson, 2003; Salthouse, 2016). Concerning memory processes, literature suggests that the most drastic deterioration occurs in recall (Hultsch, 1969; Petersen et al, 1992; Hertzog et al, 2010), whereas recognition is only moderately affected (Jacoby, 1999; Ratcliff et al, 2004; Spaniol et al, 2006; Van Ocker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%